Teacher’s action zone in facilitating group dynamics - Galajda, Dagmara (Linguarum Arena, 2018)
As believed by many researchers (Dörnyei & Murphey 2003, Hadfield 1992), classroom climate is strongly determined by the dynamics of the learning group and its development over time. For this reason, the role of the teacher in facilitating group processes seems to be of primary importance since it is the teacher who has long been regarded as the group leader in both teacher-centred and learner-centred classrooms. The presentation focuses not only on positive but also on negative forms of classroom dynamics together with management techniques for dealing with conflicts, educational alienation and psychological defensiveness. This, in turn, leads to the concept of facilitator style based on Heron’s (2006) model of facilitation, which consists of six dimensions and three modes. In the paper particular emphasis is placed on the presentation and comparison of various theories of leadership, namely Heron’s system of facilitation, Hersey and Blanchard’s situational-leadership theory (1982) and Bass and Avolio’s transactional versus transformational leadership theory (1984).